Climate Change in the Newsroom: Journalists' Evolving Standards of Objectivity When Covering Global Warming. (August 2014) - Hiles, Sara Shipley; Hinnant, Amanda
This study investigated how highly experienced environmental journalists view the professional norms of objectivity when covering climate change over time. Elite journalists were sought, and all had a minimum of 10 years of experience in climate coverage. In-depth interviews revealed a paradox: Most still profess belief in objectivity even as they reject or redefine it. Participants said that journalists should use objective practices and refrain from revealing their own biases, including advocating for the environment. However, participants have radically redefined the component of objectivity known as "balance." They now advocate a "weight-of-evidence" approach, where stories reflect scientific consensus.